Guillain Barre Syndrome after vaccination against Corona Virus Disease19: Managed in limited resource setting - Kamar, Sher Bahadur; Bhatta, Uttam Kumar; Singh, Ratna; Paudel Timilsana, Manju (Journal of Nepal Health Research Council, 2023)
A 16-year-old boy who classically featured Guillain Barre Syndrome (GBS) after Corona Virus Disease-19 vaccination was timely treated successfully in limited resource setting in far western province. After Moderna (mRNA COVID 19 Vaccine) vaccination, he rapidly developed ascending paralysis of limbs without autonomic and sensory or cranial nerve involvement. He has been treated with Intravenous Immuno-Globulin (IVIG). Over six-weeks long observation and supportive care and he was discharged with full recovery. Many GBS cases after vaccination have been reported but yet to know the association of vaccine. It is very important to address the complication for successful vaccination programme.Keywords: Complication; COVID-19; guillain barre syndrome; vaccine